A Compendium Of Two Decades Of Economic Evaluations In Dementia And A Critique Of The Implied Use Of Resources. (20th December 2022) - Trepel, Dominic
Abstract: Background: This paper presents a unified source of all health economic evaluations related to four categories of resource allocation in dementia (identification, pharmaceuticals, non‐pharmacological interventions and management strategies) and, for health professionals (i.e. non‐economists), we provides guided critiques of implied trade‐offs across varying allocation decisions. Methods: To take stock of the entirety of economic evidence, we systematically review, and quality assess, all peer reviewed cost‐effectiveness analyses published since 1999. We provides in‐depth expert guidance, and objective critical appraisal, through the variety of implied inferences related to potential allocation decisions and avoid sources of underlying biased. We explain how to interpret, and differentiate between, the two common forms of economic evidence (i.e., trial‐based or model‐based cost effectiveness analysis). We illustrate strengths and weaknesses of our included studies and, towards informing optimal resource allocation, we detail the opportunities and threats in relation to quality of evidence. Results: Since 1999, we found 127 published economic evaluations (identification, 20%; pharmaceuticals, 45%; non‐pharmacological approaches, 18% and; management strategies, 17%). Internationally, the top five countries producing economic evaluations in dementia were: UK (33%); USA (19%); the Netherlands (10%) Canada (7%) and; (jointly) Germany/Sweden (5%). Over time, production of economic evidence appears relatively flat (averaging 1 to 2 publications per category) but significant upsurges in pharmaceutical‐related studies occurred in 2005 (n = 5), 2010 (n = 8) and 2012 (n = 8). Reporting is generally found to meet objective international standards, however, our critique of model‐based techniques raises concerns. Examining funding sources, industry‐funded pharmaceutical studies appear more likely to report more favourable cost effectiveness results, with these exclusively simulation‐based studies often purporting more cost savings (as compared to publicly‐funded studies). Notwithstanding concerns, the sum of evidence indicates that, compared to usual dementia care, alternative resource allocation can often result in increased quality‐of‐life, whilst also reducing costs. Conclusion: In contrast to competing disease areas, dementia research has experienced a relatively low production of economic evidence. Given the considerable economic changes created by dementia, and potential for economic benefit highlight here, increasing the inclusion of high quality economic evaluations alongside dementia‐related research is required.